A giraffe and a half - Silverstein, Shel. (New York : HarperCollins Publishers, 1964)
A cumulative tale done in rhyme featuring a giraffe unto whom many kinds of funny things happen until he gradually loses them.
NP
Accelerated Reader AR
Keywords: Nonsense verses, American; Children's poetry, American; Stories in rhyme; Giraffe -- Fiction